INTERFACE OF CONTROLLERSHIP ARTIFACTS AND THE LIFE CYCLE IN FAMILY BUSINESSES - Caresia, Francieli Diane Merlin (Seven Editora, 2024)
The study analyzes whether family businesses are in harmony with the use of controllership artifacts, according to the study by Miller and Friesen (1984), with regard to the evolution of the life cycle linked to succession. The research is identified as a multiple, descriptive and qualitative case study. The sample is composed of two family businesses in the State of Santa Catarina, one in the food industry, located in the municipality of São Lourenço do Oeste - SC and the other in the trade activity - Supermarkets, located in Chapecó - SC, both operating in the market for more than 30 years. Data collection was directed to the person responsible for the controllership of the companies under study, through a questionnaire, which was sent by e-mail. The results show that controllership artifacts are part of the reality of the companies studied, and that they emphasize controllership as an important tool for managers’ decision-making. It is possible to verify that both organizations are in the maturity phase, with regard to the stage of the life cycle. DOI:https://doi.org/10.56238/sevened2024.037-029